Ovarian Torsion Management and Its Long-Term Impact on Ovarian Reserve: A Clinical Review - Ojha, Pranav; Kadel, Lakhan Bhaskar; Riyazuddien, Shaik.; Darney, Ebby (Journal of Global Economy, Business and Finance, 2025)
Background: Ovarian torsion constitutes a gynaecological emergency most commonly seen in the reproductive age group. The aim of the study was to find out the ovarian reserve in the affected ovary after conservative surgery of ovarian torsion. Antral follicle count measured via transvaginal ultrasound was used for the same. Method: It is a retrograde study. All the cases with ovarian torsion who underwent conservative surgical procedure in the institute from January 2020 - January 2023 were studied. The demographic date, including patient’s age, presenting complaints, Details of clinical presentation, laboratory findings like haemoglobin, leucocyte count and platelet count were noted. All the cases with features of sepsis and malignancy were excluded from the study. Antral follicle count was checked in the three month follow up ultrasonography. Results: In our study, all cases on follow up ultrasound had a follicle count between 6 - 12 in the affected ovary suggestive of preserved ovarian function. Conclusion: The study shows that conservative surgery following ovarian torsion had preserved ovarian reserve as observed by the antral follicle count in the preserved ovary on transvaginal ultrasound. We recommend it as the first line treatment irrespective of the intraoperative appearance of the ovary.